Association Between Triglyceride Glucose Index and Non-Small Cell Lung Cancer Risk in Chinese Population - Yan, Xin; Gao, Yujuan; Tong, Jingzhi; Tian, Mi; Dai, Jinghong; Zhuang, Yi (Frontiers in Oncology, 2021)
Background: Numerous studies showed that insulin resistance (IR) was associated with cancer risk. However, few studies investigated the relationship between IR and non-small cell lung cancer (NSCLC). The aim of this study is to explore the association of the triglyceride glucose (TyG) index, a simple surrogate marker of IR, with NSCLC risk. Methods: 791 histologically confirmed NSCLC cases and 787 controls were enrolled in the present study. Fasting blood glucose and triglyceride were measured. The TyG index was calculated as ln [fasting triglycerides(mg/dl) ×fasting glucose (mg/dl)/2]. Logistic regression analysis was performed to estimate the relationship between NSCLC risk and the TyG index. Results: The TyG index was significantly higher in patients with NSCLC than that in controls (8.42±0.55 vs 8.00±0.45, P<0.01). Logistic regression analysis showed that the TyG index (OR=3.651, 95%CI 2.461-5.417, P<0.001) was independently associated with NSCLC risk after adjusting for conventional risk factors. In addition, a continuous rise in the incidence of NSCLC was observed along the tertiles of the TyG index (29.4% vs 53.8% vs 67.2%, P<0.001). However, there were no differences of the TyG index in different pathological or TNM stage. In receiver operating characteristic (ROC) curve analysis, the optimal cut-off level for the TyG index to predict incident NSCLC was 8.18 and the area under the ROC curve (AUROC) was 0.713(95% CI 0.688–0.738). Conclusions: The TyG index is significantly correlated with NSCLC risk and it may be suitable as a predictor for NSCLC.